2019
DOI: 10.1016/j.molcel.2019.06.034
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase SIRT6 Restrains Transcription Elongation via Promoter-Proximal Pausing

Abstract: Highlights d The histone deacetylase SIRT6 binds to Pol II and promotes transcriptional pausing d SIRT6 retains NELF by deacetylating intragenically H3K9 and H3K56 d Removal of SIRT6 from chromatin increases K9/K56 acetylation d Recruitment of elongation factors promotes transcriptional elongation of SIRT6 targets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 107 publications
4
43
0
Order By: Relevance
“…In comparison, genes bound only by MYC demonstrated lower RNAPII pausing index but still retained a transcriptional level comparable to genes bound by both factors. Consistent with these findings, it has previously been shown that genetic ablation and chemical inhibition of LSD1 in pluripotent cell lines (mouse ESCs and F9 cells) increased the level of H3K56ac 64 , a histone modification associated with the gene body 2 and recently identified as a key histone mark, along with H3K9ac, that modulates transcriptional pausing and elongation 58 . In another study, LSD1 ablation and catalytic inhibition led to an upregulation of H4K16ac 64 , a histone mark that has been implicated in the regulation of RNAPII promoter-proximal pausing by recruiting BRD4 and P-TEFb 65, 66 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In comparison, genes bound only by MYC demonstrated lower RNAPII pausing index but still retained a transcriptional level comparable to genes bound by both factors. Consistent with these findings, it has previously been shown that genetic ablation and chemical inhibition of LSD1 in pluripotent cell lines (mouse ESCs and F9 cells) increased the level of H3K56ac 64 , a histone modification associated with the gene body 2 and recently identified as a key histone mark, along with H3K9ac, that modulates transcriptional pausing and elongation 58 . In another study, LSD1 ablation and catalytic inhibition led to an upregulation of H4K16ac 64 , a histone mark that has been implicated in the regulation of RNAPII promoter-proximal pausing by recruiting BRD4 and P-TEFb 65, 66 .…”
Section: Discussionsupporting
confidence: 65%
“…The co-localization of LSD1 and CDK9 was observed at both promoter and enhancer elements, where CDK9 have been shown to be involved in enhancer-associated RNAPII pausing 17, 56, 57 . A recent study has demonstrated a functional role of SIRT6, a histone deacetylase, in the release of RNAPII pausing by preventing the eviction of NELF-E from the chromatin 58 , highlighting the direct involvement of chromatin remodellers in RNAPII pausing and release.…”
Section: Discussionmentioning
confidence: 99%
“…The ChIP data is presented as log 2 (ChIP/input) as nucleosome density is not consistent between the different gene bins. h The average signal relative to the TSS for PRO-seq 74 , and H3K9ac and H3K27ac ChIP-seq data relative to all genes (green) or 3035 transcribed genes that have low (blue) or high (red) upstream PRO-seq signal. …”
Section: Resultsmentioning
confidence: 99%
“…SIRT6 can also bind p53 to effectively recruit RNAP2 to local promoters ( Li et al, 2018 ). SIRT6 deficiency mediates the activation of cyclin-dependent kinase 9 (CDK9) that can phosphorylate negative elongation factor (NELF) and mediate NELF release from RNAP2, facilitating the enrichment of TFs and RNAP2-related elongation factors to promote elongation of specific gene sets ( Etchegaray et al, 2019 ). Consistently, TSA and SAHA disturb RNAP2-mediated transcriptional elongation by promoting the association between RNAP2 and NELF ( Greer et al, 2015 ).…”
Section: Biological Functions Of Hdacsmentioning
confidence: 99%